Oddaję do rąk czytelnika książkę, która pomoże ustrzec się choroby - wstęp w dawnym i współczesnym poradniku zdrowia - Błachowicz, Ewa (Słowo. Studia językoznawcze, 2013)
The subject of analysis in the present article is the introduction in health guides, its features, structure and language. The accumulated data refer to publications from 19 th , 20 th and 21 st centuries. The primary aim is not to specify similarities or differences between introduction, foreword in former and contemporary health guides; the main aim was to show the continuity and consequences of the form which introduces the main body of text and constitutes its escort. The presentation of the gathered material proves that the form, structure, principles of the introduction are largely kept in a similar convention; they have similar references and relate to a identical type of content (they present the message sender, the aim and premises of the publication, invite to read). The construction as well as language schemes are repeated. This creates a certain formal and thematic continuity where diversity is noticed with reference to available medication, type of treatment, medical knowledge, the form of addressing the recipient. It is not an exaggeration to state that introduction is one of the most difficult but at the same time interesting forms of linguistic expression, it is the reflection of the time which illustrates as well as the treasury of available knowledge and the place where the author is most visibly presented.